Bằng chứng mới về tác động bất đối xứng của thay đổi tỷ giá hối đoái lên giá chứng khoán tại Việt Nam - Huỳnh Thái, Huy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
Most of the previous studies on the relationship between exchange rates and stock prices have assumed that the adjustment in two variables is symmetrical. This paper aims at investigating the asymmetric effects of exchange rate changes on stock prices in VN. Based on the monthly data in 01/2001–01/2017 and adopting the nonlinear autoregressive distributed lag (NARDL) approach, the paper demonstrates the presence of cointegration among the variables including stock prices, positive and negative elements of exchange rates, money supply and inflation. Besides, the results reveal that stock prices make a significantly asymmetric response to currency appreciation and depreciation; in addition, currency appreciation has more considerable impacts on stock prices in the long run than the depreciation does.
Keywords: Stock market; Foreign exchange market; Asymmetry; NARDL